Ferroelectric polarization promoted electrocatalytic hydrogen evolution on Bi2Fe4O9 nanoplates. (15th July 2023) - Xu, Guang-Rui; Wang, Jing; Zhang, Ning; Zhang, Qiong; Dong, Zemeng; Zhang, Wen; Wu, Zexing; Xie, Cong-xia; Wang, Lei
Abstract: Unconventional ferroelectricity exhibited by Bi-based nanosheets presents potential opportunities in catalytic fields, whereas the polarization characteristic remains controversial in electrocatalysis. Herein, we report a novel ferroelectric catalyst of polarized Bi2 Fe4 O9 nanoplates through the corona poling method after hydrothermal and calcination processes, exhibiting super catalytic activity for water splitting controlled by ferroelectric switching and special two-dimensional (2D) structure. The ferroelectric polarization depending on high voltage greatly enhances the activity of polarized Bi2 Fe4 O9 nanoplates for hydrogen evolution reaction (HER) with a 98 mV positive shift of overpotential compared to the unpolarized Bi2 Fe4 O9 nanoplates in alkaline conditions. And after long-term stability tests, the polarized Bi2 Fe4 O9 nanoplates exhibit excellent durability for hydrogen production. Our results show that the effect of ferroelectric polarization of Bi2 Fe4 O9 nanoplates enhances the electrocatalytic hydrogen evolution, which provide a new strategy for broad the application of ferroelectric materials. Graphical abstract: The polarized Bi2Fe4O9 nanoplates boost the hydrogen evolution reaction (HER) with a 98 mV positive shift of overpotential compared to the unpolarized Bi2Fe4O9 nanoplates ascribed to the adjusted d-band center and special two-dimensional (2D) structure. Image, graphical abstract